2014
DOI: 10.1093/gbe/evu072
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian-Specific Sequences in Pou3f2 Contribute to Maternal Behavior

Abstract: Various mutations have occurred during evolution among orthologs, genes in different species that diverged from a common ancestral gene by speciation. Here, we report the remarkable deterioration of a characteristic mammalian maternal behavior, pup retrieval, in nonmammalized mice, in which the transcription factor Pou3f2 was replaced with the Xenopus ortholog lacking all of the homopolymeric amino acid repeats of mammalian POU3F2. Most of the pups born to the nonmammalized mice died within days after birth, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Previous studies have indicated that male mice have a weaker ability to identify novel objects compared with female mice (Frick & Gresack 2003;Ghi et al 1999;Sutcliffe et al 2007), consistent with our observation. Our present observation is also consistent with our previous finding of impaired pup recognition in Pou3f2 Δ/Δ dams (Nasu et al 2014). In the object location test, Pou3f2 Δ/Δ mice also exhibited impairments in spatial cognition.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous studies have indicated that male mice have a weaker ability to identify novel objects compared with female mice (Frick & Gresack 2003;Ghi et al 1999;Sutcliffe et al 2007), consistent with our observation. Our present observation is also consistent with our previous finding of impaired pup recognition in Pou3f2 Δ/Δ dams (Nasu et al 2014). In the object location test, Pou3f2 Δ/Δ mice also exhibited impairments in spatial cognition.…”
Section: Discussionsupporting
confidence: 93%
“…Our present observation is also consistent with our previous finding of impaired pup recognition in Pou3f2 Δ/Δ dams (Nasu et al . ). In the object location test, Pou3f2 Δ/Δ mice also exhibited impairments in spatial cognition.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, deletion of the polyglutamine tract in mouse huntingtin results in subtle behavioural changes relating to learning and memory and motor coordination [63]. Replacement of mouse POU3F2 with a Xenopus orthologue that lacks polyglutamine tracts and other homopolymer amino acid repeats resulted in neurochemical changes and a dramatic deterioration in pup retrieval behaviour [64]. The polyglutamine tract in mouse SRY has important roles in protein stabilization and transcriptional activation that are essential for sex determination [65].…”
Section: Discussionmentioning
confidence: 99%